2010
DOI: 10.1177/1538574410373663
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Analysis of Infrapopliteal Percutaneous Transluminal Angioplasty and Bypass Graft Surgery With Nonreversed Saphenous Vein for Individuals With Critical Limb Ischemia

Abstract: Both BGS and PTA provided similar results of patency and limb salvage for individuals with infrapopliteal atherosclerotic disease presenting with CLI. Bypass graft surgery had better results than PTA when TASC D lesions were present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
0
13
0
3
Order By: Relevance
“…Cependant, les taux de perméabilité secondaire et de sauvetage de jambe étaient plus élevés pour le pontage que pour l'angioplastie pour les patients avec des lésions TASC D à 12 mois de suivi (p = 0,04 et 0,01, respectivement) [27].…”
Section: Que Disent Les éTudes Qui Comparent Ces Deux Techniques ?unclassified
“…Cependant, les taux de perméabilité secondaire et de sauvetage de jambe étaient plus élevés pour le pontage que pour l'angioplastie pour les patients avec des lésions TASC D à 12 mois de suivi (p = 0,04 et 0,01, respectivement) [27].…”
Section: Que Disent Les éTudes Qui Comparent Ces Deux Techniques ?unclassified
“…In the overall series and in the propensity score, matched pairs PTA and bypass surgery achieved similar 6 months leg salvage, survival and amputation-free survival rates. Both provide an acceptable limb salvage rate, but patency appears to be better after bypass surgery [1,9,15]. The greatest problem in treating lower limb ischaemia and trying to compare different methods of treatment is that it is very difcult to standardize the disease itself.…”
Section: Discussionmentioning
confidence: 99%
“…The limb salvage rate after PTA is higher than the angiographic patency rate. Patients with long lesions in infrapopliteal arteries are usually offered a bypass surgery [1]. Direct pedal bypass is performed most frequently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found similar outcomes between angioplasty and bypass for infrapopliteal TASC A, B, and C lesions; however, outcomes are not as favorable for TASC D lesions. 10,11 As technology for infrapopliteal angioplasty and stents improves, it is possible that the proportion of interventions performed with endovascular techniques will increase, approaching that seen with femoral-popliteal disease.…”
Section: It Ismentioning
confidence: 98%